2017
DOI: 10.1038/srep45527
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted metabolomics analysis reveals key pathways responsible for the synergistic killing of colistin and doripenem combination against Acinetobacter baumannii

Abstract: Combination therapy is deployed for the treatment of multidrug-resistant Acinetobacter baumannii, as it can rapidly develop resistance to current antibiotics. This is the first study to investigate the synergistic effect of colistin/doripenem combination on the metabolome of A. baumannii. The metabolite levels were measured using LC-MS following treatment with colistin (2 mg/L) or doripenem (25 mg/L) alone, and their combination at 15 min, 1 hr and 4 hr (n = 4). Colistin caused early (15 min and 1 hr) disrupti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
70
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 73 publications
15
70
1
Order By: Relevance
“…The increased permeability of the outer membrane is supported by our fractional inhibitory concentration results (Tables S5 to S7), in which the enrofloxacin MICs decreased in the presence of polymyxin B and vice versa. Additionally, the mechanistic data from polymyxin-doripenem combination against A. baumannii also showed a similar mechanism of synergy (56). The exclusion of either aspect of the synergy mechanism from the MBM resulted in a model that could not be estimated, as the simplified model provided poor curve fits (R 2 of Ͻ0.50; data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…The increased permeability of the outer membrane is supported by our fractional inhibitory concentration results (Tables S5 to S7), in which the enrofloxacin MICs decreased in the presence of polymyxin B and vice versa. Additionally, the mechanistic data from polymyxin-doripenem combination against A. baumannii also showed a similar mechanism of synergy (56). The exclusion of either aspect of the synergy mechanism from the MBM resulted in a model that could not be estimated, as the simplified model provided poor curve fits (R 2 of Ͻ0.50; data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…Colistin kills bacteria by membrane disruption which simultaneously increases meropenem entrance into bacteria (17). It had been reported that the synergy of colistin and carbapenems (doripenem) was time-dependent inhibition of different metabolic pathways in a metabolomics study (18). Colistin induced disruption of bacterial lipids and metabolic changes via pentose phosphate pathway metabolism in early stages.…”
Section: Discussionmentioning
confidence: 99%
“…In this order of ideas metabolomics can be an important strategy for elucidate the synergistic metabolic pathways that can be selected as antimicrobial targets and optimizing antibiotic pharmacokinetics/ pharmacodynamics that avoid resistance emergence [11].…”
Section: Synergismmentioning
confidence: 99%